THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN SHAPING CUSTOMER LOYALTY AT MCDONALD'S FAST FOOD OUTLETS IN THE JABODETABEK AREA - Muhammad Ariq Farabi; Muhammad Marcello Bujung; Mohammad Rafi Arya Dwi Putra; Nur Riftisah (Indonesian Marketing Journal, 2022)
The aim of this research is to analyze and know the impact of service quality in shaping customer’s loyalty through customer’s satisfaction. The research uses non-probability purposive sampling technique and the research is quantitive research. The research uses questionnaires as the instrument to collect the data and analyzed with SEM. The total collected data are about 150 respondents. The result of the data research shows that, has five dimensions affect the service quality positively and the other results tells that customer’s satisfaction is a major factor to customer’s loyalty. The result of the research shows that there is no any direct relation between service quality and customer’s loyalty, so the direct effect of service quality on customer’s loyalty does not sustain on the research.